Predictors of Participation in Mammography Screening among Non-Hispanic Black, Non-Hispanic White, and Hispanic Women - Melvin, Cathy L.; Jefferson, Melanie S.; Rice, LaShanta J.; Cartmell, Kathleen B.; Halbert, Chanita Hughes (Frontiers in Public Health, 2016)
Introduction: Many factors influence women’s decisions to participate in guideline recommended screening mammography. We evaluated the influence of women’s socioeconomic characteristics, healthcare access, and cultural and psychological healthcare preferences on timely mammography screening participation. Materials and methods: A random digit dial survey of United States non-Hispanic Black, non- Hispanic White, and Hispanic women ages 40-75, from January-August 2009 determined self- reported time of most recent mammogram. Screening rates were assessed based on receipt of a screening mammogram within the prior 12 months, the interval recommended at the time by the American Cancer Society. Results: Thirty-nine percent of women reported not having a mammogram within the last 12 months. The odds of not having had a screening mammography was higher for non-Hispanic White women than for non-Hispanic Black (OR=2.16, 95% CI=0.26, 0.82, p=0.009) or Hispanic (OR=4.17, 95% CI=0.12, 0.48, p=0.01) women. Lack of health insurance (OR=3.22, 95% CI=1.54, 6.73, p=0.002) and lack of usual source of medical care (OR=3.37, 95% CI=1.43, 7.94, p=0.01) were associated with not being screened as were lower self-efficacy to obtain screening (OR=2.43, 95% CI=1.26, 4.73, p=0.01) and greater levels of religiosity and spirituality (OR=1.42, 95% CI=1.00, 2.00, p=0.05). Neither perceived risk nor present temporal orientation was significant. Discussion: Odds of not having a mammogram increased if women were uninsured, without medical care, non-Hispanic white, older in age, not confident in their ability to obtain screening, or held passive or external religious/spiritual values. Results are encouraging given racial disparities in healthcare participation and suggest that efforts to increase screening among minority women may be working.